Afghan Pilgrimage Routes to Arabia (1100–1900 CE): A Historical–Geographical Analysis of Religious Logistics and the Caravanserai Network - Mazloum Yar, Fayaz Gul; Sadaat, Sayed Habibullah (Fakultas Ilmu Budaya, Universitas Jambi, 2025)
This study presents a historical–geographical reconstruction of overland pilgrimage routes used by Afghan Hajj pilgrims between 1100 and 1900 CE. By integrating geo-referenced historical maps, GPS-verified field surveys, and classical pilgrimage narratives, the research examines the spatial configuration of caravanserai infrastructure and the evolution of religious logistics across multiple political and environmental contexts. Through Geographic Information Systems (GIS) and spatial network analysis, the study identifies a small-world structure within the caravanserai network, highlighting five central hubs that served as critical points for provisioning and connectivity. Temporal segmentation of the network reveals shifts in node density and service typologies under Seljuk, Ilkhanid, Timurid-Safavid, and Qajar-Afghan rule. The findings contribute to the fields of historical geography and pilgrimage studies by offering a replicable framework for analyzing sacred mobility systems. They also inform heritage conservation strategies and sustainable pilgrimage logistics in arid and mountainous contexts.